DyMMer 2.0: A Tool for Dynamic Modeling and Evaluation of Feature Model - Bezerra, Carla; Lima, Rafael; Silva, Publio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Managing dynamic variability has motivated several researchers to combine Dynamic Software Product Lines (DSPLs) practices with runtime variability mechanisms. By combining these approaches, a DSPL acquires important features, ranging from the ability to reconfigure by changing the context, adding or removing features, crash recovery, and re-adaptation based on changes in the model’s features. Feature model (FM) is an important artifact of a DPSL and there is a lack of tools that support the modeling of this artifact. We have extended the DyMMer tool for modeling FM of DSPLs from an adaptation mechanism based on MAPE-K to solve this problem. We migrated the DyMMer tool to a web version and incorporated new features: (i) modeling of FMs from SPLs and DSPLs, (ii) development of an adaptation mechanism for FM of DSPLs, (iii) repository of FMs, (iv) inclusion of thresholds for measures, and (v) user authentication. We believe that this tool is useful for research in the area of DSPLs, and also for dynamic domain modeling and evaluation. Video: https://youtu.be/WVHW6bI8ois